Islamic Perspectives on Theory Building in the Social Sciences (American Journal of Islam and Society, 1993)
The issue of the relevance of Islam to modem "scientific" thinking isflanked on both sides by extreme positions. On further investigation,however, these positions tun out to reflect certain misconceptions only,perpetuated by certain structural and pemnal factors that lend themselvesreadily to systematic analysis and, hopefully, correction. On the one hand,we have legions of Muslim social scientists who still flinch at hearing ofattempts to integrate divine revelation with science. Many of them wouldfind the title of this paper problematic, if not outright self-contradictory.What does Islam, or any other religion for that matter, have to do withscience or with theory building, they would ask.This response should hardly be unexpected, considering the type ofacademic and professional indoctrination that we all have gone through.The scientific establishment, with its overriding positivist-empiricistleanings, has long adopted and encouraged an attitude-or more correctlya "faith"-of sepamtion between science and religion. Consider, for example,the following statement by no less an authority than the NationalAcademy of Sciences in the United States, in 1981:Religion and science are separate and mutually exclusive realmsof human thought, presentation of which in the same contextleads to misunderstanding of both scientific theory and Feligiousbelief. (Sperry 1988, 608-9)This terse statement is representative of the attitudes of those whoadhere to the old paradigm, seemingly totally oblivious of the fundamentalcriticisms leveled from all directions at that type of outmodedview of science.On the other hand, we have those Muslim scientists already active inthe Islamic science movement who may find the content of the paper objectionablebecause it does not depart enough from the Western model of ...